Erucismo: etiología, epidemiología y aspectos clínicos en San Ignacio, Misiones, Argentina (Revista Venezolana de Salud Pública, 2019)
An entomological and descriptive clinical-epidemiological study of the series of cases of erucism in Municipio de San Ignacio, Misiones, between 2015 and 2018, was carried out due to the extraordinary increase in accidents reported by non-systematic sources. In order to know the etiology, epidemiological aspects, symptoms and injuries, interviews were conducted with semi-structured surveys and the caterpillars responsible for the accidents were collected. We compiled 719 cases of erucism, and we identified Podalia orsilochus, an unprecedented etiological agent to date in Argentina, as the main responsible (91%; n = 653) together with other six other species of Megalopygidae and Saturniidae. We found that erucism has season al risk and February is the month with the highest number of accidents. The rate of urban cases tripled that of rural cases, related to contact with plants by 49%. The inoculation of the venom of the bristles generated a histamine-like dermal syndrome with diffuse neuritis, adenopathy, systemic manifestations, persistence of symptoms, petechial lesions and necrosis in the area of contact. The latter can have two types of sequelae: scar and hyperchromia. The 68% of the affected population demanded health care, and the most affected were adults and young people, who experienced between two and three days of work disability.  In conclusion, the emerging event of erucismo is described, recognizing for the first time Podalia orsilochus, the epidemiological aspects and immediate morbidity that show the need to intensify the diffusion of prevention, entomological monitoring and clinical-epidemiological surveillance that allows to identify these sanitary events and to adapt in time-space the preventive actions and of adequate attention.
Keywords: Stinging caterpillar; Podalia orsilochus